Covalent Electrografting of Aryl Groups on Aa2060-T8 Surfaces, and Their Modification with Ce(4ohcin)3 to Incorporate Additional Anticorrosive Activity - Paez-Collio, M; Paez-Collio, M; Azocar-Guzman, M; Azocar-Guzman, M; Silva-Molina, C; Silva-Molina, C (Elsevier Editora Ltda, 2024)
The aluminum alloys used in aerospace applications are susceptible to corrosion. This has led to the development of methodologies that ensure the durability of the parts and pieces of aircraft. These anticorrosive processes involve the use of coatings containing chromate-based corrosion-inhibitor compounds. Although these coatings provide an excellent solution to this problem, their use in protection protocols is restricted owing to their high toxicity and carcinogenic nature. This study evaluates a different process to protect aluminum alloy surfaces that incorporates the derivatization of organic compounds using potentiostatic techniques. The metallic surface was modified in situ by the potentiostatic reduction of aryl diazonium salts, leaving the surface covered with molecular grafts. The grafting of molecules onto the surface is modulated by the application of a potential that causes the formation of aryl radicals. The organic compound selected in this study was p-toluidine in protic medium. The derivatization process in the AA2060-T8 alloy was carried out at different pHs and potentials, observing from the potential/current responses in 0.1 M NaCl solution that the maximum optimization is obtained at pH 3 and -1 V. Likewise, the E/I and electrochemical impedance (EIS) responses of the electrografted samples modified and functionalized with cerium 4-hydroxycinnamate (Ce(4-OHcinn)3) revealed that the presence of this compound in the arylic structure significantly increased the protective capacity of the organic film electrografted on the aluminum alloy. The morphologies and characteristics of the modified surface were studied by SEM, TEM, and XPS. Furthermore, TEM examinations of ultramicrotomed sections of the electrografted specimens revealed the presence of a film approximately 10 nm thick on the AA2060-T8 surface. © 2024 The Authors